Effectiveness of impermeable core on the reduction of seepage flow in dike - Guo, Felicia ZhiYin. (2013)
Dikes system has been constructed over decades to protect people’s life and infrastructures from flooding. Once the dike fails, the consequence will be catastrophic. One of the most common reasons for dike to fail is seepage flow through dike. To minimise the occurrence of seepage flowing, clay core is being constructed within dike.